Enhancement of ring and ripple microelectrodes design using dielectrophoresis (DEP) for biochip application - Siti Nursyahirah, Ahmad Latfi (2018)
Nowadays, the need for the analysis of biological cells has become a platform for researchers to develop related technologies and devices for conducting appropriate manipulation such as trapping, screening, and sorting. This is because the analysis of biological cells can be beneficial to better understand the properties of biological cells and find the solution and treatment in medical applications. Various manipulation techniques have been developed to manipulate biological cells such as manipulation technique in chemical, mechanical, acoustic and electric fields. The DEP was force used to manipulate the cells resulting from the generation of a non-uniform AC electric field and electrode patterns play a major role in producing the required electric field. The current design has limitations in terms of the distribution pattern of the electric field generated and insufficient simulation data required for the development of biochip. There were two new electrodes which are ring pattern microelectrode and ripple pattern microelectrode developed in this study. The main objective of this work is to investigate the electric field distribution resulted from the microelectrodes. All analyses performed in this study were based on simulations. Simulations were carried out by using COMSOL Multiphysics software, which provides suitable simulation and analysis platform for this study. The optimisation of an electrode was done by making some modifications to the dimensions of the electrodes and simulated with different electrical potential values. This was done to improve the performance of the electrodes to trap a single cell. Based on the simulation results obtained, the highest strength of the electric field distribution was generated by the ring electrode pattern 5.22  106 V/m produced and the DEP force was 1.42  10-13N. The ripple pattern electrode generated 2.04  107 V/m of electric field and the DEP force produced was 4.19  10-11 N which was higher than the ring electrode. It was found that the temperature rise issues can be controlled based on simulation results by reducing the voltage by half, yet electric field can generate higher electric field strength. The percentage increase in electric field strength of ring microelectrode and ripple microelectrode was 86.86% and 47.55%, respectively. The results showed that the distance between the microelectrodes and micro-cavity provided more impact in electrical field distribution strength compared to the change of the microelectrodes dimension. The resulting electrical field strength was high between the microelectrodes tip and edge of the micro-cavities. Cell trapping may also occur in the central part of the micro-cavities with nDEP where the cells were attracted to the areas of low electric field. On the other hand, when pDEP was used, cells were attracted to the edge of micro-cavities where the high electric field region occurred. With the simulation and analysis obtained, designed microelectrode was able to trap the cells. This research work became an attempt to find a biochip design, in order to get the better electrode design patterns which offered higher efficiency in manipulating and trapping the biological cells.